Monitoring biodiversity combining environmental and social data - Allard, Anna; Keskitalo, E. Carina H.; Brown, Alan (2023)
This book is an exciting reappraisal of the role and practice of biodiversity monitoring, showing how new technologies and software applications are rapidly maturing and can both complement and maintain continuity with the best practice in traditional field skills. Environmental monitoring is a key component in a large number of national programmes and constitutes an important aspect of understanding environmental change and supporting policy development. Taking an interdisciplinary approach, Monitoring Biodiversity begins by discussing monitoring as an established field and examines the various budgetary and technological challenges. It examines different methodologies, the variation between countries and the design features relevant to understanding monitoring systems created for new policy goals or different funding situations. The huge variety of methods revealed across 18 chapters, which vary from statistical designs to remote sensing, interviews, surveys, and new ways of stacking and combining data and thematic information for visualisation and modelling, underlines just how mature and multi-faceted the modern practice of monitoring can be. It concludes with several problem-based chapters which discuss the design and implementation of environmental monitoring in specific scenarios such as urban and aquatic areas. All chapters include a section on key messages, study questions and further reading. With a focus on Europe, but with international relevance, Monitoring Biodiversity will be an essential resource for students at all levels of environmental monitoring, assessment and management"--